Oral liarozole in the treatment of patients with moderate/severe lamellar ichthyosis: results of a randomized, double‐blind, multinational, placebo‐controlled phase II/III trial. (January 2014) - Vahlquist, A.; Blockhuys, S.; Steijlen, P.; van, K.; Didona, B.; Blanco, D.; Traupe, H.
<x xml:space="preserve">Abstract</x> What's already known about this topic? Oral liarozole, a retinoic acid metabolism‐blocking agent, may be an alternative to systemic retinoid therapy for patients with lamellar ichthyosis. What does this study add? While the primary endpoint was not met, compared with placebo, once‐daily oral liarozole, 75 or 150 mg, decreased overall severity and scaling, but not erythema and pruritus, and improved Dermatology Life Quality Index in patients with lamellar ichthyosis. Oral liarozole was well tolerated.